2006
DOI: 10.1063/1.2356606
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication and structural characterization of highly ordered sub-100-nm planar magnetic nanodot arrays over 1cm2 coverage area

Abstract: Porous alumina masks are fabricated by anodization of aluminum films grown on both semiconducting and insulating substrates. For these self-assembled alumina masks, pore diameters and periodicities within the ranges of 10-130 and 20-200 nm, respectively, can be controlled by varying anodization conditions. 20 nm periodicities correspond to pore densities in excess of 10 12 per square inch, close to the holy grail of media with 1 Tbit/ in. 2 density. With these alumina masks, ordered sub-100-nm planar ferromagn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
41
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 42 publications
(42 citation statements)
references
References 49 publications
1
41
0
Order By: Relevance
“…20,21 The nanodots have been grown on silicon substrates with a diameter of 67± 13 nm and a thickness of 20 nm, similar to those reported earlier. 19 The Fe dots thus made are polycrystalline, capped with a Ag layer.…”
mentioning
confidence: 72%
“…20,21 The nanodots have been grown on silicon substrates with a diameter of 67± 13 nm and a thickness of 20 nm, similar to those reported earlier. 19 The Fe dots thus made are polycrystalline, capped with a Ag layer.…”
mentioning
confidence: 72%
“…23 The nanodot size is 67±13 nm, and coexistence of SD and VS modes is expected from our prior studies on unbiased Fe dots. 24,25 The dot center-to-center spacing is roughly twice the dot diameter, as illustrated in Fig.…”
mentioning
confidence: 99%
“…19 Powder x-ray diffraction shows that the hexagonally ordered Fe dots are polycrystalline. By controlling the anodization process ͑i.e., electrochemical parameters͒ and using double anodization 20 dot diameters and periodicities in the range 25-150 nm with narrow distributions ͑10-15 standard deviation͒ are produced.…”
Section: Methodsmentioning
confidence: 99%
“…9,19,[25][26][27] Earlier calculations have shown that when the side-to-side distance in an array is larger than a single-dot diameter ͑i.e., the center-tocenter distance larger than twice the diameter͒ the dots interact weakly. 9 Since the dots are polycrystalline, we neglect the crystalline anisotropies.…”
Section: Theoretical Calculationsmentioning
confidence: 99%